2019
DOI: 10.4103/jcvjs.jcvjs_52_19
|View full text |Cite
|
Sign up to set email alerts
|

PROMIS physical health domain scores are related to cervical deformity severity

Abstract: Introduction:The aim of this study was to evaluate the association of available cervical alignment components through the Ames cervical deformity (CD) classification parameters with the Patient-Reported Outcomes Measurement Information System (PROMIS) physical health domain metrics.Methods:Surgical CD patients (C2–C7 Cobb >10° or C2–C7 sagittal vertical axis [cSVA] >4 cm or T1 slope minus cervical lordosis (TS-CL) >15°) ≥18 years with available baseline (BL) radiographic and PROMIS were isolated in a single-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Advancements in CD research over the past several years has broadly improved our basic understanding of sagittal deformity and compensatory mechanisms within the cervical spine. 18,19 We now recognize the contributions of the global chain of correlation and the efforts of the cervical spine to maintain horizontal gaze with its wide range of motion. 20 As the literature on CD grows, it is important to investigate whether these improvements in understanding translated into better surgical outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Advancements in CD research over the past several years has broadly improved our basic understanding of sagittal deformity and compensatory mechanisms within the cervical spine. 18,19 We now recognize the contributions of the global chain of correlation and the efforts of the cervical spine to maintain horizontal gaze with its wide range of motion. 20 As the literature on CD grows, it is important to investigate whether these improvements in understanding translated into better surgical outcomes for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical C2-C7 sagittal vertical axis (C2-C7 SVA) was investigated in 9 of the included studies 4,16,19,21,24,[26][27][28][29] , including 3 studies by the ISSG 16,19,30 . Meta-analyses of correlation coefficients showed that C2-C7 SVA and NDI correlated fairly [Random Effect; Zr = 0.31 [95% CI: -0.03, 0.58]; P < .001) 16,24,27,28,31 .…”
Section: Association Of Cervical Alignment Parameters and Prosmentioning
confidence: 99%
“…Only one study investigated the relationship between C2-C7 SVA categories in CD Ames-ISSG severity groups (Score 0, C2-7 SVA < 4 cm; Score 1, C2-7 SVA 4-8 cm; Score 2, C2-7 SVA > 8 cm), and PROMIS domains showing no difference in PROMIS scores between C2-C7 SVA categories 4 . The authors used conditional tree analysis to determine thresholds for PROMIS domains that were independent of C2-C7 SVA severities, but did not reach statistical significance 4 .…”
Section: Association Of Cervical Alignment Parameters and Prosmentioning
confidence: 99%
See 2 more Smart Citations